Studies in the Antrodia serialis group (Polyporales, Basidiomycota) - Spirin, Viacheslav; Vlasák, Josef; Miettinen, Otto (Mycologia, 2017)
Taxonomy and phylogeny of the Antrodia serialis group are revised with morphological, ecological, and geographic data, partial translation elongation factor 1-α (tef1) gene sequences, and nuc rDNA ITS1-5.8S-ITS2-28S sequences. The group contains 13 species found in boreal and temperate zones of the Northern Hemisphere. The species are limited to certain geographic areas within Eurasia and North America. The traditional morphology-based concept of A. serialis covers at least four closely related species: A. serialis s. str. in Eurasia, A. angusta, sp. nov., in East Asia, A. serrata, sp. nov., in the American Northeast, and A. calcitrosa, sp. nov., in the American Northwest. They all are associated mostly with Picea spp. and show small, but stable morphological differences from each other. In addition, A. morganii, comb. nov., inhabiting wood of Populus spp., occurs in North America, and Antrodia alaskana, comb. nov., a large-pored species, macroscopically similar to A. variiformis, is distributed along the Pacific coast of North America. The pine-dwelling A. flavimontis, sp. nov., similar to A. primaeva from Eurasia, is so far known only from the eastern part of the Rocky Mountains (Utah and Wyoming).
Keywords: DNA fungální; Antrodia; elongační faktor 1; mezerníky ribozomální DNA; DNA, Fungal; ribozomální DNA; phylogeny; sekvenční analýza DNA; taxonomy; Mycological Typing Techniques; Peptide Elongation Factor 1; DNA, Ribosomal; DNA, Ribosomal Spacer; Phylogeny; Brown-rot fungi; fylogeneze; mykologické určovací techniky; Sequence Analysis, DNA